Perbandingan Dosis Serap Bolus Berbahan Playdough, Plastisin, dan Silicone Rubber pada Radioterapi Berkas Elektron 6 MeV dan 9 MeV - Pramita, Niken; Adrial, Rico; Ilyas, Muhammad (Universitas Andalas, 2023)
Comparison of absorbed dose bolus made from playdough, plasticine, and silicone rubber in electron beam radiotherapy has been assessed. This study aims to compare the absorbed dose, calculate the Relative Electron Density (RED) value, and physical density of playdough, plasticine, and silicone rubber bolus. The boluses were made with dimension of 15 cmÃ—15 cm and thickness of (0,5; 1,0; 1,5; and 2,0) cm. RED value was obtained from tomographic image using CT-Simulator by determining 5 Region of Interest (ROI) regions. The physical density was calculated based on the mass and volume ratio. The absorbed dose was measured using a plan parallel chamber detector with a Linear Accelerator (LINAC) energy variation of 6 MeV and 9 MeV. The results are playdough, plasticine, and silicone rubber bolus have a homogeneous material composition with RED values is above the RED of water. The physical density of playdough and plasticine bolus is above the density of skin tissue but lower than bone tissue, while the physical density of silicone rubber bolus is close to the density of water, muscle, liver, kidney, and lung tissue. The absorbed dose value of silicone rubber bolus with a thickness of 0.5 cm is closer to the absorbed dose without bolus, so bolus of silicone rubber that are better used at energy of 6 MeV and 9 MeV are silicone rubber bolus.